Socialinės teisės Europos žmogaus teisių teismo praktikoje - Jočienė, Dr. Danutė Danutė (Teisė, 2008)
The present Article deals with the question of interpretation of social rights in the jurisprudence of the European Court of Human Rights (thereafter – the Court)1. In the article the Author analyses the social rights’ issues under the European Convention on Human Rights and their interpretation given by the European Court of Human Rights. Social rights were not included into the text of the Convention adopted in 1950. Nevertheless, the Court has opened the door for a new interpretation of human rights enshrined in the Convention taking into account the social issues of the rights involved and setting up new tendencies for their full and effective implementation at international and national levels. Different social rights’ issues, arising in the applications submitted to the Court, especially in the last years, raise the discussion whether exclusion of social rights can still be regarded as legitimate and where there is already a need to include expressly the social rights into the text of the Convention or, whether, the protection of social rights is sufficient under the provisions of the European Social Charter and under the broader interpretation of such rights provided for by the European Court of Human Rights.Straipsnyje analizuojama socialinių teisių aiškinimo ir taikymo klausimai Europos žmogaus teisių teismo praktikoje. Pažymėtina, kad socialinės teisės nebuvo įtrauktos į Europos žmogaus teisių konvencijos tekstą, priimtą 1950 m., todėl peticijos dėl socialinių teisių gynimo buvo atmetamos kaip nesuderinamos su Konvencijos nuostatomis. Ilgainiui, vykstant socialiniams pokyčiams ir plečiantis teisių, numatytų Konvencijoje, aiškinimo ir taikymo riboms, Europos žmogaus teisių teismas ėmė aiškinti Konvencijoje numatytas teises plačiau, apimdamas ir atitinkamus socialinių teisių aspektus. Straipsnyje taip pat keliamas klausimas, į kurį kol kas negalima rasti vienintelio atsakymo, ar ne laikas būtų aiškiai įtraukti socialinių teisių kategoriją į Europos žmogaus teisių konvencijoje numatytų teisių sąrašą, ar vis dėlto užtenka Teismo plečiamo aiškinimo šių teisių atžvilgiu bei Europos socialinės chartijos nuostatų.